Business-IT Alignment: A Discussion on Enterprise Architecture and Blockchains. Editorial Introduction to Issue 35 of CSIMQ - Erika Nazaruka (Complex Systems Informatics and Modeling Quarterly)
Nowadays, business operation is impossible without proper alignment between business and IT goals. The alignment foresees integration at different levels: strategic, managerial, technological, and others. In addition, aligning goals should take into account factors arising from interaction with business partners, competitors, customers, and supervisory authorities. The collection of articles included in this issue presents research on the impact of different factors on the achievement of business and IT goal alignment. The first two articles in the collection concern Enterprise Architecture (EA) while the last two articles consider blockchain applications.